2022
DOI: 10.1590/1982-0216/20222465622
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Following Response and Auditory Middle Latency Response: an analysis of central auditory processing in young adults

Abstract: Purpose: to compare the latency and amplitude of the Frequency-Following Response and the Auditory Middle Latency Response in typical individuals and those with altered auditory abilities, as well as to investigate the sensitivity and specificity of both assessments in relation to central auditory processing. Methods: 32 individuals of both sexes were distributed into Group 1 (without altered auditory abilities) and Group 2 (with altered auditory abilities). The groups were divided according to behavioral tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that the MLR is modulated by differences in interaural time and intensity cues, which are important for sound localization and binaural fusion [ 29 ]. Furthermore, the MLR has been shown to be associated with the perceptual grouping of sounds, such as the segregation of speech from background noise [ 37 , 38 ]. However, the literature on the MLR in binaural hearing is limited, and more research is required to comprehend its role in binaural hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the MLR is modulated by differences in interaural time and intensity cues, which are important for sound localization and binaural fusion [ 29 ]. Furthermore, the MLR has been shown to be associated with the perceptual grouping of sounds, such as the segregation of speech from background noise [ 37 , 38 ]. However, the literature on the MLR in binaural hearing is limited, and more research is required to comprehend its role in binaural hearing.…”
Section: Introductionmentioning
confidence: 99%